Sibol revitalizing the community center for a sustainable future - Santillan, Rafael Vien A.; Madrid, Dolores Cecilia T. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
Sibol is a redevelopment of the town center of barangay Maybunga in Pasig City. Located at the heart of the barangay -- it is an overhaul of the existing infrastructure with the use of a modified land readjustment scheme. It is how I envision the development for the rest of Pasig City, using architecture not only for aesthetic development but also for solving inherent issues faced by the community. As the name literally implies Sibol which means to grow, progress and develop. The project aims to design an infrastructure that challenges the urban fabric by creating a transit-oriented, people-centric and forward-looking development.
Include appendices
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Shopping centers; Shopping centers -- Philippines -- Pasig City